2017
DOI: 10.5004/dwt.2017.20817
|View full text |Cite
|
Sign up to set email alerts
|

Drinking water treatment using upflow slow sand filtration systems in high density Cylindrospermopsis raciborskii cyanobacteria water

Abstract: a b s t r a c tCyanobacterium Cylindrospermopsis raciborskii may cause problems in drinking water treatment plants if specific attention is not focused on removing the cyanobacteria. Slow sand filtration possesses a good capacity for cyanobacteria removal and is a simple alternative to more expensive treatments. However, high cyanobacteria concentrations can correspond to an operational problem for slow sand filters by reducing the filter running time, and therefore rough filtration is necessary. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…A. ambigua, other diatoms, and filamentous cyanobacteria were the most common microorganisms present (Figure 3, 3 and 8). These microorganisms appearance is not surprising since they are common on the Lagoa do Peri water and were previously reported as filter clogging phytoplankton (de Souza et al, 2017;Saavedra del Aguila and Di Bernardo, 2003;Saupe and Mosimann, 2003). Cyanobacteria are highlighted in this study because of their abundance in the raw water, especially the genera Cylindrospermopsis and Pseudanabaena.…”
Section: Other Microrganisms Composing Biomasssupporting
confidence: 53%
See 2 more Smart Citations
“…A. ambigua, other diatoms, and filamentous cyanobacteria were the most common microorganisms present (Figure 3, 3 and 8). These microorganisms appearance is not surprising since they are common on the Lagoa do Peri water and were previously reported as filter clogging phytoplankton (de Souza et al, 2017;Saavedra del Aguila and Di Bernardo, 2003;Saupe and Mosimann, 2003). Cyanobacteria are highlighted in this study because of their abundance in the raw water, especially the genera Cylindrospermopsis and Pseudanabaena.…”
Section: Other Microrganisms Composing Biomasssupporting
confidence: 53%
“…Previous studies suggested backwashing for SSF cleaning as an alternative to scraping (de Souza et al, 2017Souza et al, , 2016Michelan et al, 2011;Pizzolatti et al, 2014). The application of backwashing is particularly recommended for medium and small-scale filters (<1m²) that can be easily applied in small and isolated communities or in small agroindustry (FUNASA, 2019;Michelan et al, 2011;Pizzolatti et al, 2014).…”
Section: Biomentioning
confidence: 99%
See 1 more Smart Citation
“…SSF is a well-known process for drinking water treatment and is widely used for the production of biologically stable drinking water and particle removal [4]. After two centuries of improvement and perfection, the SSF has been characterized by the following advantages: 1) good removal efficiency of bacteria, viruses, and organic material; 2) simple structure that is easy to construct; 3) independence from the gravitydriven automatic inflow as only one mechanical piece of equipment, a water pump, is necessary -no other automatic or electronic equipment is required, making it easy to operate; and 4) it is not necessary to add any chemical agent, which avoids the risk of transportation and storage of chemical agents and avoids the production of by-products due to chemical disinfection (e.g., the production of chloramines due to the addition of chlorine for disinfection) [5][6].…”
Section: Ssfmentioning
confidence: 99%
“…The reduction started at Week 6 and total elimination was reached in Week 9 and later. It suggested that slow sand filtration could remove other plant pathogenic viruses.deSouza et al (2017) investigated the removal of cyanobacteria Cylindrospermopsis raciborskii using upflow slow sand filtration process. High concentration of cyanobacteria was tested with removal efficiency of 99%, but the resultant concentration warranted complementary treatment for better water quality Sabiri et al (2017).…”
mentioning
confidence: 99%